The independence of the auditors - fact or fantasy / Allan Chang Aik Leng - Allan, Chang Aik Leng (Institut Teknologi Mara Cawangan Sarawak, 1989)
This article analyses the auditors' dilemma in projecting their image of independence in appearance and in fact. The first part will discuss the statutory provisions and ethical considerations aimed at projecting the auditors' independence in the audit of limited companies. The second part will detail the problems which arise in practice and which threaten the auditors' independence. Not all companies, whether private or public, are subject to an audit. Only companies which are registered under the Malaysian Companies Act 1965 (as amended) are obliged to undergo an external audit at least once a year. These are "limited companies." In the event of a bankruptcy, the shareholders' liability is limited to the share capital they have contributed while their personal assets remain untouched.